Pengaruh Model Pembelajaran Kooferatif Learning Tipe Picture and Picture Terhadap Hasil Belajar Siswa Kelas II pada Mata Pelajaran Matematika - Vitria, Rina Nur; Usamah, Asep (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Mathematics learning still faces challenges in increasing student engagement and understanding of abstract concepts. The dominance of conventional learning methods such as lectures causes the learning process to be teacher-centered, resulting in students being less active in building conceptual understanding. Studies on the picture-to-picture cooperative learning model in mathematics learning are still limited, particularly in explaining the role of visual representations in understanding mathematical concepts. This study aims to analyze the effect of implementing the picture-to-picture cooperative learning model on students' mathematics learning outcomes and identify its contribution in supporting conceptual understanding. This study uses a qualitative approach with a literature study method through the analysis of various relevant previous research articles. Data are analyzed descriptively to obtain an overview of the implementation and effectiveness of the model in mathematics learning. The results of the study indicate that the picture-to-picture cooperative learning model can improve students' mathematics learning outcomes through the use of images as a representation medium that helps connect abstract concepts with visual experiences. This model also encourages student activity, cooperation, and involvement in the learning process. Thus, picture-to-picture can be an alternative learning strategy to improve the quality of mathematics learning.